KEPEMIMPINAN TRANSFORMASIONAL KEPALA MADRASAH PEREMPUAN DALAM PENINGKATAN KEDISIPLINAN KINERJA GURU DI MADRASAH ALIYAH PERGURUAN MU'ALLIMAT (MAPM) - Wifqi Syarah Izzati; Moh. Syamsul Falah (Jurnal Manajemen Pendidikan, 2026)
Teacher discipline is a determining pillar of educational success in madrasahs, and the quality of the principal's leadership is a crucial factor in shaping such discipline. This study aims to examine the application of transformational leadership by female madrasah principals, the condition of teacher performance discipline, and the role of such leadership in improving teacher performance discipline at Madrasah Aliyah Perguruan Mu'allimat (MAPM) Jombang. The study used a qualitative approach with a case study design. Data were collected through in-depth semi-structured interviews, participant observation, and institutional documentation review, then analyzed using the Miles and Huberman interactive model with data validity guaranteed through triangulation of sources and techniques. The results show that female madrasah principals at MAPM consistently apply the four dimensions of transformational leadership: building a culture of discipline through exemplary behavior (idealized influence), mobilizing shared commitment through systematic vision communication (inspirational motivation), facilitating continuous professional development (intellectual stimulation), and personally assisting teachers through an empathetic-dialogical approach (individualized consideration). Teacher performance discipline at MAPM is considered high, reflected in the average teacher attendance above 91% per month, a structured substitute teacher system, zero empty classes, and the fulfillment of all pedagogical and administrative obligations.